CATCH WAGE SHARING STUDY PURSE SEINE SHIP AT PT. HASIL LAUT SEJATI (HLS) BATAM RIAU ISLANDS - Yaser Krisnafi; Roma Yuli F Hutapea; Rio Arianda Simarmata; Suci Asrina Ikhsan; Djunaidi Djunaidi (Aurelia Journal, 2023)
Wages are compensation received by workers based on their position. The division of the catch has been stated in several regulations, namely Law Number 16 of 1964 article 3 and Minister of Maritime Affairs and Fisheries Regulation Number 42 of 2016 article 26. The purpose of this research was to determine the catch on purse seine vessels, the organizational structure of wages, and the application of profit sharing systems and crew wages on purse seine at PT Hasil Laut Sejari (HLS). Data collection was carried out 3 times. Position at KM. Sumber Fortuna influences the wages received by the ship's crew. The total catch production for 3 trips is 64,463 kg. Distribution of wages for crew members (ABK) per 1 part, the first trip to the third trip. The wages received by the crew on the first trip were Rp. 162,402,-. on the second trip Rp. 1,335,547, - and on the third trip Rp. 963,181, - according to Law no. 16 of 1964 and Permen KP Number 42 of 2016, the distribution of wages is not ideal because the wages received by ABK are very small and far below the Riau Islands Province Minimum Wage.